ANALISIS RASIO PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK: Indonesia - Rais, Muhammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study analyzes the profitability level of PT Bank Negara Indonesia (Persero) Tbk for the period 2020-2024 using the ROA, ROE, BOPO, and NPM ratios to evaluate financial performance. Descriptive analysis methods and financial ratios show a significant upward trend in profitability. ROA increased from 0.59% (2020) to 2.45% (2024), reflecting the efficient use of assets. ROE also increased from 4.63% (2020) to 17.18% (2024), indicating increased returns for shareholders. The BOPO ratio decreased from 81.85% (2020) to 72.17% (2024), indicating improved operational efficiency. Meanwhile, NPM increased from 5.81% (2020) to 22.66% (2024), confirming stable net profit growth. These results are in line with BNI's transformation program which focuses on improving asset quality, low-risk credit expansion, and digitalization. This study concludes that BNI has managed to maintain solid profitability despite external challenges, with a sustainable strategy to achieve the 20% ROE target by 2028.